Diretrizes curriculares e a formação de professores de geografia na rede municipal de educação de Goiânia (2005 - 2012) - Viana, Inez Maria Milhome (2015)
This present search sought to reflect about Geography teachers' continue development by means of "Grupos de Trabalho e Estudo" (GTE) – Curriculum, that had as objective the reformulation of "Diretrizes Curriculares para a Educação Fundamental da Infância e da Adolescência na Rede Municipal de Educação de Goiânia", and the reflex of this process in the context of teacher's pedagogic practice. These professionals increased their conceptions about "Ciclos de Formação e Desenvolvimento Humano"? How do these subjects understand and linke the essential principles of " Proposta Pedagógica da RME e das Diretrizes Curriculares" that they helped to elaborate? What changes in pedagogic practice can be attributed to the teachers' participation in GTE? The investigation was by qualitative approach, using as procedure the documental research, the application of questionnaires to collect the data about teachers' participation in Geography GTE and the implications of this participation in their pedagogic practice, in addition the participant observation in the classroom, characterized by the interaction between researcher and researcher subjects. The obtained results allowed to conclude that GTE of Curriculum establishes in an important formative space to exchange ideas, of experiences and discussion among pairs, favoring directly teacher's action in the scholar institution. This motivated the elaboration of one proposal of the project of Geography teacher's development, as one of the resulting products of the search.